Breeding System and Phytochemical Analysis of Orthosiphon aristatus Blume (Miq.) - Nur Karimah, Mohamad (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Orthosiphon aristatus (Blume) Miq. is a perennial herb under the mint family, Lamiaceae. The study on O. aristatus was conducted with several aims to accomplish which include (1) to study the breeding system of O. aristatus through artificial pollination, (2) to determine the flower developmental at which the pollen is most viable, (3) to investigate the potential of flavonoids as phytochemical markers, and (4) to determine whether there is any significant effect of different drying conditions on the flavonoid profiles of O. aristatus. In artificial pollination tests, two tests conducted which were self-pollination and cross pollination. All artificial pollination tests were considered as successful if seeds were developed. Pollen viability test were conducted using in vitro germination method and the pollens were collected from three different developmental stages; pre-anthesis, anthesis and post-anthesis. Whilst, for the phytochemical marker analysis of flavonoids, two dimensional paper chromatography (PC) was utilised as the separation technique. Retention factor (Rf) value was calculated for each compound observed and the flavonoid profiles of OAV-1 and OAV-2 were compared. Lastly, the different drying conditions were imposed on the O. aristatus samples to see if there is any significant effect on the flavonoids content of the leaf samples. From the study conducted, O. aristatus was suggested to be a pre-dominantly self-pollinated species with the support of pollen viability test that indicated viable pollen can be observed during pre-anthesis stage. The flavonoid profiles of OAV-1 and OAV-2 showed polymorphism which can be used as marker in breeding program. Drying quality test revealed that temperature plays important factor in the flavonoid contents of O. aristatus C) caused degradation of flavonoid contents